Prospective Association Between Tobacco Use and at-Risk Alcohol Consumption Among Swedish Adolescents: Outlining the Influence of Tobacco Product, Frequency of Use and Gender in the LoRDIA Cohort - Johanna Andersson; Kristina Berglund; Robin Irmel; Louise Adermark (SAGE Publishing, 2024)
Introduction: Tobacco use is not only a major risk factor for morbidity and mortality but also associated with alcohol misuse. While personality traits may be driving this association, the psychoactive component of tobacco, nicotine, may also be a major risk factor. The aim with this study was to further assess the prospective association between tobacco use and alcohol consumption, with special emphasis on the role of the tobacco product used (cigarettes and Swedish snus), frequency of use, and gender. Methods: Data was extracted from the prospective cohort Longitudinal Research on Development In Adolescence (LoRDIA), following Swedish adolescents over four waves (∼13 to 17 years of age). Tobacco use was reported with respect to product used and frequency of use, while alcohol use was assessed using AUDIT-C, as well as frequency of use within the last year. Results: Use of tobacco, independent of product used and gender, was associated with increased alcohol consumption. High frequency of use and dual use strengthened to association. Individuals initiating tobacco use during the study period progressively increased their frequency of alcohol consumption compared to non-users during consecutive waves. Furthermore, tobacco use was associated with at-risk consumption of alcohol at follow up, even when adjusting for previous alcohol inebriation, socioeconomical factors, gender and novelty seeking. Conclusions: The data presented here suggests that nicotine use during adolescence, and especially dual use, is a major risk factor for future hazardous alcohol intake. This finding is especially important considering the escalated use of nicotine pouches, which in many ways resembles Swedish snus. From a public health perspective, preventive measures and policies designed to counteract all forms of nicotine use among youths is warranted.